Evaluation Model Of Noble Moral Education For Students In Madrasah - Nasaruddin , Nasaruddin; Syarifuddin, Syarifuddin; Arisandi , Bustomi (LPPPM STAI Darul Hikmah Bangkalan, 2023)
This article aims to find out the model for evaluating noble character education by schools or institutions in instilling noble character values for students in the madrasah environment. The background of this research is that teachers and institutions have not carried out a systematic evaluation of the noble character education program for students. This type of research is program evaluation research. This evaluation is used to evaluate the noble character education program for students at Madrasah Aliyah Negeri in Bima. The approach used in this type of research is a quantitative and qualitative descriptive approach. The subjects in this evaluation were class XII students, the head of the Madrasah, Class XII Aqidah Akhlak Subject Teachers, and the Madrasah Committee at Madrasah Aliyah Negeri Bima. The data sources used in this study were questionnaires, documentation and interviews. The results of this study indicate that the evaluation model that is suitable for use by teachers and institutions is the Stake's Countenance evaluation model developed by Robert Stake. The Stake's countenance evaluation model consists of three stages, namely the antecedent (preparation stage), transaction (implementation stage), and outcome (result) stage. And this model is very appropriate for evaluating the noble character education program at Madrasah Aliyah in Bima, because these stages are interrelated with one another.